2022
DOI: 10.1111/een.13141
|View full text |Cite
|
Sign up to set email alerts
|

How many cooperators are too many? Foundress number, reproduction and sex ratio in a quasi‐social parasitoid

Abstract: In the parasitoid genus Sclerodermus, multiple foundresses produce and care for communal broods on large hosts, which can lead to greater reproductive success for group members than attempting to reproduce alone. We explore the consequences of foundress group size on the benefits of cooperative brooding and on brood sex ratios by providing groups of 10–55 foundresses with a single host and no alternative reproductive options. Within this range, increasing foundress group size leads to increasingly common failu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 89 publications
3
9
0
Order By: Relevance
“…Even though single foundresses achieve higher per capita production of adult offspring, inter-foundress relatedness and large host size may combine to reduce selection against communal reproduction. In Sclerodermus , single foundresses achieve little success when hosts are large, and thus per capita production of adult offspring is higher among multi-foundress groups ([ 65 ]; see also [ 66 ]).…”
Section: Contests and Parasitoid Socialitymentioning
confidence: 99%
See 1 more Smart Citation
“…Even though single foundresses achieve higher per capita production of adult offspring, inter-foundress relatedness and large host size may combine to reduce selection against communal reproduction. In Sclerodermus , single foundresses achieve little success when hosts are large, and thus per capita production of adult offspring is higher among multi-foundress groups ([ 65 ]; see also [ 66 ]).…”
Section: Contests and Parasitoid Socialitymentioning
confidence: 99%
“…Subsequently, if hosts are successfully suppressed, Sclerodermus co-foundresses may cooperatively tend the communally produced brood, but also exhibit differential reproduction (reproductive skew) according to body size asymmetries and temporal priority [ 71 ], with directly aggressive, and sometimes fatal, contest interactions between females observed [ 37 ]. Further, foundresses appear to be competing over the sex ratios that they contribute to the communal broods, via pre- or post-ovipositional dominance and/or infanticide [ 66 , 71 ], as explored by recent game-theoretic modelling [ 72 ]. Overall, the quasi-sociality exhibited by Sclerodermus is cooperative to a degree but is also condition-dependent and involves conflicts of interest, competition and contests.…”
Section: Contests and Parasitoid Socialitymentioning
confidence: 99%
“…A remaining puzzle is the extent of the sex ratio bias produced by species in the cooperatively brooding (“quasi-social”) parasitoid genus Sclerodermus (Hymenoptera [sub-clade Aculeata]: Bethylidae): sex ratios at offspring maturity are typically around 0.1 (10% offspring are males) and appear little influenced by the number of co-reproducing foundresses (e.g., Abdi et al, 2020b , 2021 ; Guo et al, 2022 ; Kapranas et al, 2016 ; Malabusini et al, 2022 ; Tang et al, 2014 ; Wang et al, 2016 ; Wei et al, 2017 ; Yang et al, 2018 ) or by the relatedness between foundresses ( Abdi et al, 2020a , b ; Guo et al, 2022 ). A proposed explanation ( Tang et al, 2014 ) is that mutually beneficial actions of co-foundress females during host attack and subsequent brood tending could select for the female bias via local resource enhancement (LRE: Taylor, 1981 ) but the size of the effect predicted by a recent formal model ( Iritani et al, 2021 ) is insufficient to explain the observed bias.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that females attune their degree of cooperation in host attack according to the risk of being wounded or killed by the resisting host by rolling and twisting its body and biting the parasitoids (Hu et al, 2012; Liu et al, 2021) and to the relatedness between the females (Abdi, Hardy, Jucker, & Lupi, 2020; Abdi, Lupi, Jucker, & Hardy, 2020; Liu et al, 2021; see also Mesterton‐Gibbons & Hardy, 2021). Although the hosts of Sclerodermus can be large and support the development of many offspring, resource competition between foundresses can occur (Malabusini et al, 2022). It has further been found that co‐foundress reproduction on suppressed hosts may be skewed in favour of larger foundresses and foundresses with temporal priority (Guo et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…It has further been found that co‐foundress reproduction on suppressed hosts may be skewed in favour of larger foundresses and foundresses with temporal priority (Guo et al, 2022). Observations that many foundresses do not produce adult sons have led to the suggestion that the highly female‐biased sex ratios of Sclerodermus broods may be the outcome of inter‐foundress competition, mediated by dominance and/or ovicide, rather than the benefits of mutually beneficial interactions (Guo et al, 2022; Lehtonen et al, 2022; Malabusini et al, 2022). None of these studies, however, presented any evidence for interactions between adult females of the overtly agonistic type that have been observed in Goniozus and other parasitoid species.…”
Section: Introductionmentioning
confidence: 99%